Government Programs, Job Search Requirements, and the Duration of Unemployment - Keeley, Michael C.; Robins, Philip K. (Journal of Labor Economics, 1985)
This paper presents an empirical analysis of how job search requirements under various government programs influence job search behavior. The analysis indicates that job search requirements exert a significant impact on certain aspects of the job search process, but not those that generally lead to a higher probability of employment. It is also found that persons who utilize intensively search activities that result in direct employer contact have much shorter durations of unemployment than persons who do not utilize such activities intensively. It is speculated that altering job search requirements to include more direct employer contact could lead to a significant reduction in unemployment.